1981
DOI: 10.1080/00288233.1981.10423393
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nutrition of legumes on a high country yellow-brown earth subsoil

Abstract: The growth and phosphate response patterns of a range oflegumes growing on an acid, infertile, high country yellow-brown earth subsoil were compared in two pot trials. All species responded strongly to added P, but foliage and soil analyses indicated that aluminium toxicity as well as P deficiency may have limited the growth of some species. Lotus peduneulatus, L. eornieulatus, the inter-specific lotus hybrid G4712, and Lupinus polyphyllus had low shoot Al concentrations, suggesting tolerance of Al toxicity. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Perennial lupin in both experiments became the dominant species at the lower fertiliser rates and is maintaining itself under the various stocking rates and methods, particularly the laxer sustained grazing management. The success of perennial lupin in acid, low P and high Al soils as well as its low P accumulation rates and preferential accumulation of Mn without toxic effects has also been reported by Davis (1981). The present trial has also shown its value on low S soils.…”
Section: Discussionsupporting
confidence: 78%
“…Perennial lupin in both experiments became the dominant species at the lower fertiliser rates and is maintaining itself under the various stocking rates and methods, particularly the laxer sustained grazing management. The success of perennial lupin in acid, low P and high Al soils as well as its low P accumulation rates and preferential accumulation of Mn without toxic effects has also been reported by Davis (1981). The present trial has also shown its value on low S soils.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, there is a lot of evidence showing pasture growth depression when soils with pH greater than 6.0 are limed. These negative effects mainly result from lime-induced P and Mg deficiencies (Sumner et al 1978), or a decrease in the availability of micronutrients (Davis 1981;Manselletal. 1984).…”
Section: Pasture Productionmentioning
confidence: 99%
“…drainage and pH > 5.8 (Davis 1981;Douglas and Foote 1994;Douglas et al 1996;Hill et al 1996a, b). In these countries, it persists in areas with summer drought and in areas with heavy winter precipitation, providing the soil is well drained.…”
mentioning
confidence: 99%